Gender roles in sourcing and sharing of banana planting material in communities with and without banana bunchy top disease in Nigeria - Nkengla-Asi, L.; Eforuoku, F.; Olaosebikan, O.; Ladigbolu, T.A.; Amah, D.; Hanna, R.; Kumar, P. Lava (MDPI, 2021)
Banana bunchy top disease (BBTD) is the most devastating disease of banana and plantain (Musa spp.). The disease spreads through the use of infected vegetative propagules and the banana aphid (Pentalonia nigronervosa) is the virus vector. This study seeks to understand the gender dimensions and sociocultural aspects of banana seed (vegetative propagule) sourcing and sharing practices among men and women farmers, and its influence on BBTD spread and disease control efforts. Data were collected from 300 banana farmers (187 men and 113 women) in BBTD and non-BBTD areas in southwest Nigeria. The results revealed that seed sharing within the communities is a social responsibility with members expected to share banana seed with the needy mainly as gifts rather than sold for cash. Men farmers mostly sourced seed from old fields, while women sourced seed from relatives. Harvesting of banana seed was predominantly the responsibility of men with women as helpers. Both men and women farmers in the non-BBTD area cultivated larger farm sizes and harvested more banana planting material than farmers in the BBTD area. The existing seed sourcing practices among men and women farmers heighten the risk of BBTD spread. Awareness raising on disease spread through infected seeds should consider gender-differentiated roles and social practices to reduce its spread within communities.